2023
DOI: 10.3390/ijms24021199
|View full text |Cite
|
Sign up to set email alerts
|

The ABA/LANCL Hormone/Receptor System in the Control of Glycemia, of Cardiomyocyte Energy Metabolism, and in Neuroprotection: A New Ally in the Treatment of Diabetes Mellitus?

Abstract: Abscisic acid (ABA), long known as a plant stress hormone, is present and functionally active in organisms other than those pertaining to the land plant kingdom, including cyanobacteria, fungi, algae, protozoan parasites, lower Metazoa, and mammals. The ancient, cross-kingdom role of this stress hormone allows ABA and its signaling pathway to control cell responses to environmental stimuli in diverse organisms such as marine sponges, higher plants, and humans. Recent advances in our knowledge about the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Two mammalian ABA receptors have been identified so far, LANCL1 and LANCL2, belonging to a three-member protein family with a limited homology with bacterial lanthionine synthetase but lacking the ability to synthesize (antibacterial) lanthionines. Recombinant LANCL1 and LANCL2 bind ABA [66,69], and their overexpression increases while their double silencing conversely abrogates ABA sensing in mammalian cells [70]. Recent studies have shown that LANCL1 and LANCL2, whose genes likely evolved by gene duplication and are located on different chromosomes, have largely overlapping functions in eliciting ABA responses in myocytes and adipocytes; in view of their role in stimulating cell glucose uptake and mitochondrial function, receptor redundancy might serve as a protective mechanism to ensure ABA responsiveness in cases of receptor mutation or genetic loss.…”
Section: The Aba-sensing System Is An Ancient Stress-sensing and -Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two mammalian ABA receptors have been identified so far, LANCL1 and LANCL2, belonging to a three-member protein family with a limited homology with bacterial lanthionine synthetase but lacking the ability to synthesize (antibacterial) lanthionines. Recombinant LANCL1 and LANCL2 bind ABA [66,69], and their overexpression increases while their double silencing conversely abrogates ABA sensing in mammalian cells [70]. Recent studies have shown that LANCL1 and LANCL2, whose genes likely evolved by gene duplication and are located on different chromosomes, have largely overlapping functions in eliciting ABA responses in myocytes and adipocytes; in view of their role in stimulating cell glucose uptake and mitochondrial function, receptor redundancy might serve as a protective mechanism to ensure ABA responsiveness in cases of receptor mutation or genetic loss.…”
Section: The Aba-sensing System Is An Ancient Stress-sensing and -Res...mentioning
confidence: 99%
“…The LANCL/ERRα/PGC-1α axis: uncoupling the yin and yang of mitochondrial function.Several feed-forward mechanisms concur in maintaining the LANCL1-2/AMPK/SIRT1/ERRα/PGC-1α axis active once "started". AMPK stimulates Nampt activity and NAD synthesis, consequently increasing SIRT1 activity; AMPK and SIRT1 post-translationally modify and activate PGC-1α; LANCL1/2 expression levels upregulate the expression of AMPK, ERRα, PGC-1α, and ERRα, which, in turn, control LANCL1/2 expression[68,70,72]. This signaling axis stimulates mitochondrial biogenesis and oxphos activity and upregulates the cell's ability to cope with increased oxidative stress at the same time, which is linked to a higher respiration capacity.…”
mentioning
confidence: 99%
“…The experimental studies have been added to give a first validation of the newly proposed LANCL2 agonist AR-42 , by comparison with the known compounds BT-11 and ABA . In detail, mitochondrial function analyses in LANCL2-overexpressing and LANCL2-silenced cardiomyocytes cells have been performed, when treated with the mentioned ligands, using the mitochondrial proton gradient (∆Ψ)-sensitive dye JC-1 [ 5 , 32 ]. Indeed, mitochondrial dysfunctions, such as excessive reactive oxygen species (ROS) production, mitochondrial Ca 2+ dyshomeostasis, the loss of ATP, and defects in mitochondrial dynamics and transport and mitophagy, are expected to have a high impact on the pathogenesis of neurodegenerative diseases such as AD [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…LANCL3 exhibits the lowest expression levels among these LANCL proteins and may even be a pseudogene [2,3]. LANCL1 was the first member of this family to be isolated from human erythrocyte membranes [4] and then to be highly expressed in the brain [1,5], while LANCL2 was subsequently recognized as expressed at the central nervous system (CNS) level, as well as in peripheral tissues, such as the immune cells, heart, placenta, lung, liver, pancreas, prostate, and skeletal muscles [6]. Furthermore, LANCL1 and LANCL2 differ in their subcellular localization: LANCL1 is mainly a cytosolic and nuclear protein, while the majority of LANCL2 is inserted into the plasma membrane by means of the myristoylated Gly residue at the N-terminal of the protein [7].…”
Section: Introductionmentioning
confidence: 99%